Ten Fashionable Years – Keeping Dyeing Chemistry from Dying - Palazzi, Sergio (Chimica nella Scuola, 2025)
Ten years have passed since the first classes graduated from Italian secondary schools, after the global reform of 2010. A brand new curriculum was introduced, oddly called “Sistema Moda - Tessile Abbigliamento e Moda”, where the former curricula in finishing and in weaving technologies are merged with other disciplines, to prepare a new kind of skilled and open minded textile technician, ready for the always changing issues of sustainable manufacturing. The article describes some significative experiences at the historical “Setificio” Institute of Como, also reflecting on some criticalities.